The Role of Foreign Direct Investment (FDI) in Regional Economic Development - Ahmad Indarto, Bambang (Yayasan Meira Visi Persada, 2026)
This study analyzes the role of foreign direct investment in promoting regional economic development in Indonesia. Using the panel data analysis method for the period 2020-2024, this research examines the impact of FDI on regional economic growth, technology transfer, and employment absorption. The results show that FDI has a significant positive impact on regional economic growth with a coefficient of 0.234. Technology spillover effects have been proven to increase domestic firm productivity by 15.2% in the same industry. FDI also successfully absorbed 650,172 workers in Q3 2024. Manufacturing and downstream sectors became the main growth drivers with a contribution of 21.6% of total investment. West Java dominates FDI absorption, with US2.5 billion, followed by Central Sulawesi at US2.1 billion. This study recommends strengthening downstream policies and improving domestic companies' technology absorption capacity to maximize FDI benefits for regional economic development.